Computational chemistry methods applications - Ramasami, Ponnadurai (De Gruyter, 2020)
This book reviews a variety of methods in computational chemistry and their applications in different fields of current research. Ab initio methods and regression analyses are discussed with special focus on their application to investigate chemical structures as for example dyes or drug compounds. Further topics are the use of computational methods in the modeling of spectroscopic data or to study reaction mechanisms.